2018
DOI: 10.21037/atm.2018.05.38
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes for total knee arthroplasty patients with active extension lag

Abstract: There was no significant difference in readmission rates; however, patients with Q-lag experienced a clinically significant higher pain level. Since this is the first study of its kind, we suggest further investigations on the effect of Q-lag on patient outcomes following primary TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This limitation has been associated with progressive degenerative changes in knee arthritis. Soft tissue and bone damage during TKA can contribute to the development of active extension lag due to pain-induced inhibition of active muscle motor units [ 24 ]. In the context of this study, which focuses on OWHTO rather than TKA, there may be an impact on the impaired knee extensor mechanism and alterations in neuromuscular function due to knee arthritis, particularly in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation has been associated with progressive degenerative changes in knee arthritis. Soft tissue and bone damage during TKA can contribute to the development of active extension lag due to pain-induced inhibition of active muscle motor units [ 24 ]. In the context of this study, which focuses on OWHTO rather than TKA, there may be an impact on the impaired knee extensor mechanism and alterations in neuromuscular function due to knee arthritis, particularly in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Because muscle hypertrophy from resistance training was observed after 7-12 weeks [14] , the intervention span in this study was considered too short for muscle hypertrophy. Previous studies have shown that muscle activation failure, also known as arthrogenic muscle inhibition (AMI), occurs after TKA and is associated with knee pain [3][4][5] . Due to structural damage, AMI is caused by swelling, in ammation, and reduced output from articular sensory receptors and occurs after knee surgery [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical invasion of the knee extension mechanism leads to a remarkable reduction in quadricep strength, especially in the acute phase after surgery [3] . This dysfunction, expressed as knee extension lag (EL), is primarily caused by failure of voluntary muscle activation [3][4][5] . Although clinical guidelines from the American Physical Therapy Association recommend performing highintensity strength exercises in the acute phase after TKA to improve muscle function [6] , this is not easy to practice because patients experience moderate to severe knee pain during this period [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Quadriceps lag (Q-lag) is the latency in the active extension caused by muscle weakness. It is defined as the patient's inability to extend the knee to the last 15 degrees of extension 2 .…”
Section: Introductionmentioning
confidence: 99%